ظاهرة تشويه صورة الإسلام والمسلمين في الغرب (دراسة وصفية تحليلية): The phenomenon of distorting the image of Islam and Muslims in the West (An analytical descriptive study) (Khairulummah, 2021)
The dissonance between Islam and the West is old and new, as it originated since ancient times, but it is increasing and growing day after day like the spread of wildfire, and it is in fact the morbid fear of Islam or what is literally known as Islamophobia, perhaps dating back to the era of the emergence of Islam and the call to it, and according to the Europeans’ description of this The term is likely to return to the Crusades, about ten centuries ago, and we note this well after the events of September 11, 2001, when what is known as the phenomenon of Islamophobia appeared clearly in the West and the European world.Regarding the relationship between the distortion of the image of Islam and the fear of it, we say that there is an overlap, and a very great link between the distortion of the image of Islam and the fear of it in what is known as Islamophobia, considering that the second is a result of the first or vice versa. We have been exposed to the other, and we urgently need to study this phenomenon in an accurate and objective scientific study through which we show the true roots of this phenomenon, and the reasons that led to its emergence, as well as looking at ways to treat it and focus on solutions and proposals to improve the image of Islam and Muslims in the West.